Pemberhentian Direksi Perseroan Terbatas Tanpa Melalui Mekanisme Rapat Umum Pemegang Saham Luar Biasa - Hajar, Siti; Ginting, Budiman; Nasution, Bismar; Sunarmi, Sunarmi (PAMALI: Pattimura Magister Law Review, 2024)
Introduction: The management of the company is the sole responsibility of the board of directors. The law does not provide. The law does not provide for the board of commissioners to give direct and permanent members of the board of directors, but is limited to temporary dismissal. This is the background for the dismissal of the directors of the Company without going through the mechanism of an extraordinary general meeting of shareholders.Purposes of the Research:  Is to know the judge's consideration of the appointment and dismissal of judges in decision number 15/pdt.g/2013/PN.Cibinong and to know the legal consequences in the dismissal of directors not in accordance with the mechanism of the extraordinary general meeting of shareholders, to achieve the objectives of this research normative juridical research is used through a statutory approach.Methods of the Research: The research method used is normative juridical with legal, conceptual, and case approaches.Results of the Research: The results of the research obtained that the implementation of the dismissal of the Board of Directors based on the decision Number 15/Pdt.G/2013/PN.Cibinong that the dismissal mechanism is not in accordance with the provisions of Law Number 40 of 2007 concerning Limited Liability Companies carried out by the Board of Commissioners of PT. SBTI, thus causing legal consequences affected to the company, namely the Minister rejects any application submitted or notification submitted to the Minister, and because the dismissal is not in accordance with the provisions, the dismissal is invalid and null and void and restore the position of the old Board of Directors who have been temporarily dismissed.The dismissal of a member of the Board of Directors is to stop the person concerned from the position of the Board of Directors before the term of office specified in the articles of association or the decision of the GMS expires. In article 106 of the 2007 Company Law, the temporary dismissal of the Board of Directors is the right and authority of the Board of Directors, but not to dismiss directly and permanently.